The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1038/sj.ijo.0802012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a ‘non-diet’ wellness intervention for improvement of metabolic fitness, psychological well-being and eating and activity behaviors

Abstract: Over a 1 y period, a diet approach results in weight loss for those who complete the intervention, while a non-diet approach does not. However, a non-diet approach can produce similar improvements in metabolic fitness, psychology and eating behavior, while at the same time effectively minimizing the attrition common in diet programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
212
4
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(238 citation statements)
references
References 43 publications
15
212
4
7
Order By: Relevance
“…Although this is not atypical for studies involving weight reduction (e.g., Dalle et al, 2005; 566 Douketis, Macie, Thabane, & Williamson, 2005; Fabricatore et al, 2009), attrition in weight-567 neutral programs has been shown to be better in comparison to conventional weight-management 568 programs (Bacon et al, 2002(Bacon et al, , 2005. Given that the attrition analyses revealed little evidence to 569 suggest characteristics that were predictive of study completion (aside from the significant 570 association with race/ethnicity), we can only speculate about what could have been done 571 differently to encourage better adherence at the 24-month follow-up.…”
Section: Internalized Weight Stigma Moderates Eating Behavior 24mentioning
confidence: 99%
See 2 more Smart Citations
“…Although this is not atypical for studies involving weight reduction (e.g., Dalle et al, 2005; 566 Douketis, Macie, Thabane, & Williamson, 2005; Fabricatore et al, 2009), attrition in weight-567 neutral programs has been shown to be better in comparison to conventional weight-management 568 programs (Bacon et al, 2002(Bacon et al, , 2005. Given that the attrition analyses revealed little evidence to 569 suggest characteristics that were predictive of study completion (aside from the significant 570 association with race/ethnicity), we can only speculate about what could have been done 571 differently to encourage better adherence at the 24-month follow-up.…”
Section: Internalized Weight Stigma Moderates Eating Behavior 24mentioning
confidence: 99%
“…drive for thinness, body dissatisfaction, poor interoceptive awareness, and depression (e.g., 84 Bacon et al, 2002;Bacon, Stern, Van Loan, & Keim, 2005; Mensinger, Calogero, Stranges, & 85 Tylka, 2016; for reviews, see Cadena-Schlam & Lopez-Guimera, 2014;Clifford et al, 2015; and 86 Schaefer & Magnuson, 2014). Although this body of research demonstrated effectiveness for 87 weight-neutral programs, what is less clear is whether there are moderators that strengthen or 88 weaken their effectiveness.…”
Section: Internalized Weight Stigma Moderates Eating Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Where interventions that focus on relaxation of restraint (a so-called 'undieting' approach) have been compared with those promoting restraint, the inclusion of restraint produces better weight loss results. [49][50][51][52] Longitudinal studies overwhelmingly show that increases in restraint over time are associated with greater weight loss, 45,[53][54][55] and also with better weight maintenance after weight loss. [56][57][58][59][60] Studies of long-term weight suppressors (people who have successfully maintained a weight loss) show that this group have high levels of restraint together with low levels of disinhibition 42,[61][62][63] and report vigilant self-monitoring of eating behaviors and weight.…”
Section: Widely Used Methods Of Measuring Dietary Restraint Confound mentioning
confidence: 99%
“…Are patients made aware of the high likelihood of failure, of the risks, and of any alternatives (Bacon et al, 2002(Bacon et al, , 2005Goodman, 1995;Lyons and Miller, 1999;Miller and Jacob, 2001: throughout this article many of the references are from studies that researched people of one gender, usually women; age and ethnicity vary between studies.)? And if not, what is going wrong in obtaining informed consent?…”
Section: Ethics As If Health Promotion Matteredmentioning
confidence: 99%